Estimation of Cardiac Function by Means of Radio-cardiographic Function Analysis - Hoffmann, G.; Lösel, E.; Kleine, N. (Nuklearmedizin - NuclearMedicine, 1978)
The radiocardiographic function analysis represents a relatively simple procedure for the clinician to collect information concerning the changes of cardiac dynamics.The advantage of this method is to register non-invasively changes in cardiac dynamics at rest and during exercise such as those of enddiastolic volume, stroke volume, endsystolic volume, ejection time and filling time, and to permit the calculation of mean ejection velocity, etc.After insertion of a cardiac catheter, it is possible to record the corresponding pressure pulse in the right ventricle or in the pulmonary vessels simultaneously.